Insights Into the Inside – A Quantitative Histological Study of the Explosively Moving Style in Marantaceae - Jerominek, Markus; Will, Maria; Claßen-Bockhoff, Regine (Frontiers in Plant Science, 2018)
This study aims to identify the histological basis for the extraordinary, fast movement of the style in Marantaceae. Although this explosive pollination mechanism was subject of many studies, quantitative measurements to document volumetric changes have never been conducted. Based on physical parameters and limitations (poroelastic time), the movement itself is by far too fast to be explained by turgor changes solely. Therefore, we address the hypothesis that the style contains elastic structures to store energy allowing the fast movement. We provide an experimental approach in Goeppertia bachemiana to identify histological differences of styles in various states, i.e., steady, unreleased, and released state. Cross and longitudinal sections were used to reconstruct the cell volume in different sectors of the style. Histological data were discussed with respect to a putative water shift (turgor movement) and elastic instabilities that were proposed to explain the style movement of Marantaceae. Current data show, that the upper epidermis is under tensile stress in the unreleased state. After style release, the lower side of the style revealed an enormous water up-take. According to our results, we hypothesize that the fast style movement of G. bachemiana is likely based on an elastically stretched upper epidermis, whereas a “soaking tissue” at the lower side presumably mediates the up curling of the style. The experimental data show that at least for G. bachemiana, physical limitations such as the poroelastic time are suitable parameters to predict movements that are based on elastic instabilities.